Phonological Variation in Hawrami subDialect of Kurdish Language - Othman, Neamat Saber; Aziz, Salm Hassan; Muhammad, Shahrazad Naib; Abdullah, Mahabad Kamil; Abdulla, Mawdud Jabar (Raden Intan State Islamic University of Lampung, Indonesia, 2024)
This paper is entitled (Phonological Changes in Hawrami Dialect (A Current Descriptive Study)). It is to identify the phonological changes that occur in the sounds of everyday words and terms of speakers of different classes of this dialect, in the different environments of their appearance in the structure of morphemes and words. It also identifies the characteristics and causes of these changes and analyzes the laws that occur in these sound changes. With the classification of the types of changes and the most important structural changes, such as compatibility (complete and incomplete), incompatibility, fall, sound formation, sound change, displacement, sound separation. Also point out the causes of their occurrence such as (gravey noise, obesity, bilibials, palatal, vocal cords and place of articulation, etc). with their place of articulation at the beginning or middle or end of words and their classification into consonants and vowels.In addition to the introduction, conclusions and sources, the research is divided into two parts: the first part consists of phonology and phonemes, rules of sentence structure, characteristics and causes of phonological changes. The second section discusses phonological changes and their types and identifies structural changes.